Magnetization and screening current in an 800 MHz (18.8 T) REBCO nuclear magnetic resonance insert magnet: experimental results and numerical analysis. (23rd August 2019) - Li, Yi; Park, Dongkeun; Yan, Yufan; Choi, Yoonhyuck; Lee, Jiho; Michael, Philip C; Chen, Siwei; Qu, Timing; Bascuñán, Juan; Iwasa, Yukikazu
Abstract: The nonuniform superconducting current distribution in a REBCO coated conductor, including a varying-field-induced screening current, is responsible for a significant magnetization effect that not only degrades the field quality of REBCO magnets, but introduces risks of overstressing the conductor. This paper presents our experimental and simulation studies on the screening current effect on an 800 MHz (18.8 T) REBCO insert (H800) that together with a 500 MHz LTS nuclear magnetic resonance (NMR) magnet (L500) constitutes the MIT 1.3 GHz LTS/HTS NMR magnet (1.3 G). To develop our simulation model, which was subsequently validated by a good agreement between simulation and experiment, we chose H800, Coil 1 of the 3-coil assembly operated alone and the entire H800, for the sources of experimental data, specifically their remnant fields after current discharge and diminished axial fields during operation. Armed with this valid model, we examined in detail the negative effects of screening current on H800, an important 1.3 G component. Our simulation indicates that the screening current, nonuniformly distributed in the REBCO conductor, not only deteriorates H800 field, both strength and homogeneity, thus that of 1.3 G, but may overstress the REBCO conductor.